THE EFFECT OF THE CONTEXSTUAL TEACHING AND LEARNING (CTL ) APPROACH ON STUDENT LEARNING OUTCOMES IN IPS COURSES - Nasruddin; Wahyuddin (Sean Institute, 2022)
The type of research in this research is experimental research. The experimental research design used in this study was One Group Pretest and Posttest, meaning that this experiment only used one class, without using the control class. As a reference, the researchers obtained the pretest scores conducted by the subject teachers before the treatment and the post-treatment test (O2 ) as a comparison. The subjects of this study were 25 students of class Vb SDN Inpres Bontokape. Contextual Teaching and Learning (CTL) is a learning approach that links the material being studied with the real life of everyday students, both in the family environment, community schools and citizens with the aim of finding the meaning of the material for their lives and learning outcomes are change . behavior that can be obtained from habits and skills in learning so as to increase student knowledge . Through the results of this study, it was found that the Contextual Teaching And Learning (CTL) Approach to Student Learning Outcomes in Social Science Subjects at SDN Inpres Bontokape was more influential than student learning outcomes taught by conventional methods in improving learning outcomes in Social Science learning for students in class Vb IPS. SDN Inpres Bontokape. Because the average score of learning outcomes for Social Science subjects (IPS) at SD Inpres Bontokape taught using the influence of the Contextual Teaching and Learning (CTL) approach is higher than those taught using conventional methods.